2010
DOI: 10.1002/rcm.4437
|View full text |Cite
|
Sign up to set email alerts
|

Detection ofα2u-globulin and its bound putative pheromones in the preputial gland of the Indian commensal rat (Rattus rattus) using mass spectrometry

Abstract: The role of pheromones and pheromone-binding proteins in the laboratory rat has been extensively investigated. However, we have previously reported that the preputial gland of the Indian commensal rat produces a variety of pheromonal molecules and preputial glands would seem to be the predominant source for pheromonal communication. The presence of pheromone-binding proteins has not yet been identified in the preputial gland of the Indian commensal rat; therefore, the experiments were designed to unravel the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
30
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 32 publications
1
30
1
Order By: Relevance
“…Therefore, they would seem to carry information that leads to aggression when perceived by male mouse and to an attraction when perceived by females12. Farnesol has been identified as the major volatile compound in the preputial gland of albino rat1013 and detected the occurrence of α2u with its bound putative pheromones (i.e., Farnesol1 and 2) in the preputial gland of house rat14. The pheromonal compound farnesol identified in the preputial gland of a rat is found to attract the opposite sex very efficiently15.…”
mentioning
confidence: 99%
“…Therefore, they would seem to carry information that leads to aggression when perceived by male mouse and to an attraction when perceived by females12. Farnesol has been identified as the major volatile compound in the preputial gland of albino rat1013 and detected the occurrence of α2u with its bound putative pheromones (i.e., Farnesol1 and 2) in the preputial gland of house rat14. The pheromonal compound farnesol identified in the preputial gland of a rat is found to attract the opposite sex very efficiently15.…”
mentioning
confidence: 99%
“…In addition, the N-terminal sequence (LEDAPRVKTPGAIGYYKI) for the 60 kDa protein was determined in Apis mellifera L. and it was reported as which involved in the antennal functions characteristic of drons [21]. In vertebrates, the pheromone carrying protein, α 2u -globulin (18)(19)(20)(21) was reported in the preputial gland of both adult [45,46] and pup [47], and urine of house rat [48] while the intensity of this protein was higher in the preputial gland of adult than the prepubertal rat. Moreover, another protein, aphrodisin (17 kDa) and Bartholin gland was also reported to be a pheromone carrier and facilitated the male copulatory behaviour [49].…”
Section: Discussionmentioning
confidence: 99%
“…Since functionally the protein would bind fatty acid or its derivatives, further analysis led us to infer that farnesol and IBMP would be the most appropriate ligands that would bind with the protein. Farnesol, in a form bound to α2u-globulin, has been identified in the perpetual gland of house rat13, and it was also shown to be an alarm pheromone for aphids38.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that transport of these chemical messages occurs when they are bound with MUPs and generate broad-ranging effects in the congeners101112. The pheromone compounds farnesol 1 and 2 identified in the preputial gland of house rat, which secretes volatiles abundantly, are bound to α2u13. Female rodents and other mammals excrete some specific volatile compounds in urine during the estrus phase of reproductive cycle.…”
mentioning
confidence: 99%
See 1 more Smart Citation